Remittances and poverty in ASEAN - Faiza Husnayeni Nahar (Cogent Economics & Finance)
Remittances have been reported as a powerful and effective tool for alleviating poverty in developing countries, including those in the Association of Southeast Asian Nations (ASEAN). An increase in income level through remittances leads to a positive change in the overall economic conditions of migrant households. They can fulfill the consumption needs and even save and invest their money as long-term goals. Hence, remittances can help migrant families escape financial issues or poverty traps. This study aims to estimate the effect of remittances on poverty levels and poverty depth in six ASEAN countries, they are: Indonesia, Thailand, the Philippines, Malaysia, Laos, and Vietnam, from 1984 to 2019. The second objective is to propose policy recommendations to sustain the impact of remittances on reducing poverty. The Ordinary Least Square (OLS) and Instrumental Variable (IV) estimation methods were conducted in this study. The findings reveal that an increase in remittances contributes more to reducing the poverty headcount than the poverty gap. The IV result also indicates a larger impact compared to OLS result, confirming that remittances are endogenous to poverty. Notably, remittances consistently demonstrate positive impacts in poverty reduction when instrumented using four variables: distance, educational attainment, government stability, and banks.